Carbonic anhydrase is not a relevant nitrite reductase or nitrous anhydrase in the lung - Pickerodt, Philipp A.; Kronfeldt, Sebastian; Russ, Martin; Gonzalez-Lopez, Adrian; Lother, Philipp; Steiner, Elvira; Vorbrodt, Katja; Busch, Thilo; Boemke, Willehad; Francis, Roland C. E.; Swenson, Erik R. (The Journal of Physiology, 2019)
Key points: Carbonic anhydrase (CA) inhibitors such as acetazolamide inhibit hypoxic pulmonary vasoconstriction (HPV) in humans and other mammals, but the mechanism of this action remains unknown. It has been postulated that carbonic anhydrase may act as a nitrous anhydrase in vivo to generate nitric oxide (NO) from nitrite and that this formation is increased in the presence of acetazolamide. Acetazolamide reduces HPV in pigs without evidence of any NO generation, whereas nebulized sodium nitrite reduces HPV by NO formation; however; combined infusion of acetazolamide with sodium nitrite inhalation did not further increase exhaled NO concentration over inhaled nitrite alone in pigs exposed to alveolar hypoxia. We conclude that acetazolamide does not function as either a nitrous anhydrase or a nitrite reductase in the lungs of pigs, and probably other mammals, to explain its vasodilating actions in the pulmonary or systemic circulations. Abstract: The carbonic anhydrase (CA) inhibitors acetazolamide and its structurally similar analogue methazolamide prevent or reduce hypoxic pulmonary vasoconstriction (HPV) in dogs and humans in vivo, by a mechanism unrelated to CA inhibition. In rodent blood and isolated blood vessels, it has been reported that inhibition of CA leads to increased generation of nitric oxide (NO) from nitrite and vascular relaxation in vitro. We tested the physiological relevance of augmented NO generation by CA from nitrite with acetazolamide in anaesthetized pigs during alveolar hypoxia in vivo. We found that acetazolamide prevents HPV in anaesthetized pigs, as in other mammalian species. A single nebulization of sodium nitrite reduces HPV, but this action wanes in the succeeding 3 h of hypoxia as nitrite is metabolized and excreted. Pulmonary artery pressure reduction and NO formation as measured by exhaled gas concentration from inhaled sodium nitrite were not increased by acetazolamide during alveolar hypoxia. Thus, our data argue against a physiological role of carbonic anhydrase as a nitrous anhydrase or nitrite reductase as a mechanism for its inhibition of HPV in the lung and blood in vivo.
CRIS-Team Scopus Importer:2022-11-17
Keywords: acetazolamide; carbonic anhydrase; hypoxia; hypoxic pulmonary vasoconstriction; nitrite; pig